Real-World Clinical Outcomes of Molnupiravir for the Treatment of Mild to Moderate COVID-19 in Adult Patients during the Dominance of the Omicron Variant: A Meta-Analysis - Chienhsiu Huang; Tsung-Lung Lu; Lichen Lin (MDPI AG, 2023)
Introduction: The therapeutic impact of molnupiravir in the Omicron variant phase is unknown. The goal of the current meta-analysis was to compare the real-world clinical outcomes of molnupiravir for the treatment of mild to moderate COVID-19 during the dominance of the Omicron variant in adult patients to that of a placebo. Methods: To be included, studies had to directly compare the clinical effectiveness of molnupiravir in treating adult COVID-19 patients to that of a placebo. Studies were included based on the following outcomes: all-cause mortality, composite outcome of disease progression, hospitalization rate, and viral load. Results: The current meta-analysis included six studies that indicated that the risk of mortality was reduced by 34%, and the risk of composite outcome of disease progression was reduced by 37% among patients who received molnupiravir. Molnupiravir was associated with faster reduction in viral loads than the placebo. There was no clinical benefit of reducing all-cause mortality in mild to moderate COVID-19 patients with high COVID-19 vaccination coverage. Conclusion: The clinical effectiveness of molnupiravir was associated with COVID-19 vaccination coverage in COVID-19 patients. There is a lack of detailed data on its effectiveness in vaccinated patients, especially those with low COVID-19 vaccination coverage.